Leadership case studies in education - Northouse, Peter Guy; Lee, Marie (Los Angeles SAGE, 2016)
A look "at leadership through the eyes of educators. The text examines how the major theories and models of leadership apply to education. [...] Peter G. Northouse, Marie Lee, and contributors from all levels of the education discipline provide readers with real-world case studies that illustrate the complex leadership challenges and issues facing educators today"--Back cover.
chapter 1. Introduction -- chapter 2. Trait approach -- chapter 3. Skills approach -- chapter 4. Behavioral approach -- chapter 5. Situational approach -- chapter 6. Path-goal theory -- chapter 7. Leader-member exchange theory -- chapter 8. Transformational leadership -- chapter 9. Authentic leadership -- chapter 10. Servant leadership -- chapter 11. Adaptive leadership -- chapter 12. Psychodynamic approach -- chapter 13. Leadership ethics -- chapter 14. Team leadership -- chapter 15. Gender and leadership -- chapter 16. Culture and leadership.
Includes bibliographic references and index.
Keywords: Leadership -- Case studies; Educational leadership